Croxhapox 1990-2000. (Gent : Croxhapox, 2000)
Batu, Susan ; Broadbent, Thomas ; Van Cauwelaert, Michiel ; Coene, Marc ; Cosijns, Sylvain ; Cotteleer, Anton ; Denys, Ward ; Devens, Zjuul ; Dondeyne, Luc ; Van Heirseele, Hans ; Herr Seele ; Kamagurka ; Paridaen, Sjoerd ; Vandekerkhove, Katrien ; Vanderhaegen, Koen ; De Vos, Ignace ; De Wilde, Johan
Overzicht Croxhapox 1990-2000 [6 p.]
10 jaar Croxhapox 1990-2000
Nederlands
boek